TOURISM DEVELOPMENT IN VIETNAM: NEW STRATEGY FOR A SUSTAINABLE PATHWAY - Le Thanh TUNG (Geo Journal of Tourism and Geosites, 2020)
Vietnam has been recognized as an emerging tourism market in recent years. Tourism has brought tremendous benefits reflected through socio-economic indicators in this country. Besides, there are many business opportunities coming from the booming of the Vietnamese tourism market. However, the tourism sector is recently facing some huge challenges to maintain sustainable development in the coming time. In this context, a new development strategy is needed to change Vietnam's tourism forward to a sustainable approach. The SWOT analysis is used to show several key aspects presenting strengths, weaknesses, opportunities, threats of Vietnam's tourism industry. Based on the analysis result, some policy implications are provided to develop the Vietnamese tourism sector forward a sustainable pathway in the future.